(3GdEMcGe aj JejjR GdaJhi Yf GdCMcGe hJUQa GdbGVi hGdEeGes - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGeCHh GdYHGS CMeO Hf EOQjS GdbQGai GdeGdci GdMeO ddg Gdedc GdeGdc HLejY GdCchGf s
(3BNQgG (B:s
(3dGSjeG ai CeQ GdOjf heG jQLY Edi GdYbGFO hgPG BNQ cJGH GdCMcGe ai JejjR GdaJGhi Yf GdCMcGe hJUQa GdbGVi hGdEeGe s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B21s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs